Pairing in few-fermion systems with attractive interactions - Zürn, Gerhard; Wenz, André Niklas; Murmann, Simon; Bergschneider, Andrea; Jochim, Selim (Physical review letters, 2013)
We study quasi-one-dimensional few-particle systems consisting of one to six ultracold fermionic atoms in two different spin states with attractive interactions. We probe the system by deforming the trapping potential and by observing the tunneling of particles out of the trap. For even particle numbers, we observe a tunneling behavior that deviates from uncorrelated single-particle tunneling indicating the existence of pair correlations in the system. From the tunneling time scales, we infer the differences in interaction energies of systems with different number of particles, which show a strong odd-even effect, similar to the one observed for neutron separation experiments in nuclei.
Gesehen am 02.08.2021